Membrane disruption properties of essential oils—a double-edged sword? - Soo, Polly Xi Yap; Yusoff, Khatijah; Swee-Hua, Erin Lim; Chong, Chou Min; Lai, Kok-Song (MDPI, 2021)
The emerging literature has suggested essential oils (EOs) as new possible weapons to fight antimicrobial resistance due to their inherent antimicrobial properties. However, the potential pharmaceutical use of EOs is confronted by several limitations, including being non-specific in terms of drug targeting, possessing a high cytotoxicity as well as posing a high risk for causing skin irritation. Furthermore, some EOs have been demonstrated to adversely affect the cellular lipid profiles and permeability of the cell membrane, which may result in undesirable outcomes for the cells. Nevertheless, owing to their naturally complex compositions, EOs still hold undiscovered potential to mitigate antimicrobial resistance, as an alternative to existing antibiotics. To address the issue of overuse in antibiotics for crops which have led to the growing threat of antimicrobial resistance globally, EOs have also been proposed as potential biopesticides. Since the perceived advantages of antimicrobial attributes in EOs remain largely unexplored, this review aims to provide a discourse into its current practical usefulness in the agricultural setting. Finally, updated bioengineering techniques with emphasis of the biopesticide potential of EOs as a means to alleviate antimicrobial resistance will be included.